Proving patriotismo Latino military recruitment service and belonging in the US - Lavariega Monforti, Jessica L.; McGlynn, Adam (Lexington Books, 2021)
"Proving Patriotismo moves beyond anecdotal discussions of the Latino military experience. The authors use empirical evidence to demonstrate how the intersection of poverty, patriotism and ethnicity create an environment where the U.S. military can increase their ranks through the service of Latinos eager for a better life and American belonging"--
Keywords: USA -- Army; Ethnische Identität; Verbesserung; Hispanos; Soziale Situation; Nationalbewusstsein; United States / Armed Forces / Hispanic Americans; Recruiting and enlistment; Hispanic Americans / Attitudes; Hispanic American youth / Social conditions; Hispanic Americans / Ethnic identity; Patriotism / United States; Social surveys / United States; Patriotism; Social surveys; United States